(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article describes the causes of skin pathologies in farm animals, their clinical signs, diagnostic approaches, as well as treatment and preventive measures. Skin diseases significantly reduce animal productivity, cause economic losses, and in some cases possess zoonotic potential. Therefore, timely identification and effective control of these conditions are of great importance in veterinary practice.